2016
DOI: 10.1111/spc3.12261
|View full text |Cite
|
Sign up to set email alerts
|

Applying Theories of Communal Motivation to Sexuality

Abstract: One important but challenging aspect of maintaining a satisfying romantic relationship is keeping the sexual spark alive. Research suggests the importance of a couple's sexual connection in the maintenance of their relationship, but sustaining high levels of desire for a partner over the course of time can be difficult. In the current review, we argue that one novel approach to understanding how couples might maintain desire and satisfaction over the course of time in their relationships is applying theories o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…Although being motivated to be responsive to a partner’s sexual needs can be associated with greater sexual well-being for both partners, if the motivation to meet a partner’s sexual needs is extreme and excludes one’s own needs—termed high unmitigated sexual communion (USC]—this is no longer associated with greater sexual well-being and, instead, may be associated with poorer well-being [16,26]. Unmitigated communion differs from communal care in that it involves self-neglect [26], see also [27]. Thus, it is possible to be high in SCS without also being high in USC, as demonstrated in prior research [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Although being motivated to be responsive to a partner’s sexual needs can be associated with greater sexual well-being for both partners, if the motivation to meet a partner’s sexual needs is extreme and excludes one’s own needs—termed high unmitigated sexual communion (USC]—this is no longer associated with greater sexual well-being and, instead, may be associated with poorer well-being [16,26]. Unmitigated communion differs from communal care in that it involves self-neglect [26], see also [27]. Thus, it is possible to be high in SCS without also being high in USC, as demonstrated in prior research [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies linking close relationships to well-being have focused on social support, while neglecting the importance of nonverbal interactions, such as sex or touch (Gallace & Spence, 2010; Impett, Muise, & Peragine, 2014). Sexual activity in romantic relationships is a nonverbal interaction often experienced as highly intimate (e.g., Muise & Impett, 2016). Moreover, the literature suggests a robust positive association between sexual frequency and well-being (e.g., Blanchflower & Oswald, 2004; Muise, Schimmack, & Impett, 2016).…”
mentioning
confidence: 99%
“…In other words, people may care for others while desiring mutual care, or they may provide care in ways that are devoid of agency and concern for their own needs. More recently, research has shown that people may also be communally motivated in specific relationship domains, such as sexuality (Muise, Impett, Kogan, and Desmarais 2013;Muise and Impett 2016). Importantly, these different forms of communal motivation have unique personal and relationship implications, which are discussed below.…”
Section: History and Definitionsmentioning
confidence: 98%